Experimental study on the effect of CO2 injection on the permeability characteristics of reservoir sandstone - Bing Liang; Yangqi Ma; Weiji Sun; Xu Qin; Guotao Shi; Bo Liang (PLoS ONE, 2025)
Using the Ordos Basin dry sandstone and sandstone saturated with different saline concentrations as research subjects, a self-developed constant temperature and pressure CO2 injection simulation device was employed to conduct permeability tests on sandstone under varying effective stresses and CO2 injection pressures. The test results indicated that during the CO2 injection process, the permeability of dry sandstone was two orders of magnitude higher than that of sandstones saturated with different saline concentrations. When the effective stress increases from 10 MPa to 28 MPa, the fissure compressibility of reservoir sandstone is influenced by the saturation of different saline concentrations, with the compressibility coefficients for 0%, 15%, and 30% saline-saturated sandstone being 0.00495 MPa⁻1, 0.00614 MPa⁻1, and 0.01879 MPa⁻1, respectively. The primary reasons for the reduced permeability of sandstone are as follows: supercritical CO2 lowers the mechanical properties of sandstone; high-concentration saline induces crystallization within the sandstone, resulting in a blockage effect. High-concentration saline increases the fissure compressibility of sandstone, decreases the permeability of the sandstone reservoir, and ultimately affects the injectability of the CO2 in the reservoir.